The Politics of Government Reform in Korea: From Tripartite to Bipartite Politicization. (November 2016) - Park, Sauk-Hee; Wilding, Mark
Government reforms in South Korea, beginning in the 1980s, moved toward deconcentration and deregulation in the 1990s and 2000s. However, the contents of the reforms under the "transformational" presidencies following democratization, which aimed to raise the quality of government and respond to increasing social polarization and political discord, did not significantly reduce state power or depoliticize policy making. Instead, state strength was consolidated through tripartite politicization: the rise of ministers as a third force in policy making vis-à-vis the president and legislature. Under the "post-transformational" presidencies of Lee Myung-Bak and Park Geun-Hye, government reforms can be summarized as bipartite politicization between the president and legislature, as ministerial power has been reduced.